Fabrication of dielectrophoretic microfluidic chips using a facile screen-printing technique for microparticle trapping - Wee, W.H.; Li, Z.; Hu, J.; Kadri, Nahrizul Adib; Xu, F.; Liu, F.; Pingguan-Murphy, Belinda (Institute of Physics, 2015)
Trapping of microparticles finds wide applications in numerous fields. Microfluidic chips based on a dielectrophoresis (DEP) technique hold several advantages for trapping microparticles, such as fast result processing, a small amount of sample required, high spatial resolution, and high accuracy of target selection. There is an unmet need to develop DEP microfluidic chips on different substrates for different applications in a low cost, facile, and rapid way. This study develops a new facile method based on a screen-printing technique for fabrication of electrodes of DEP chips on three types of substrates (i.e. polymethyl-methacrylate (PMMA), poly(ethylene terephthalate) and A4 paper). The fabricated PMMA-based DEP microfluidic chip was selected as an example and successfully used to trap and align polystyrene microparticles in a suspension and cardiac fibroblasts in a cell culture solution. The developed electrode fabrication method is compatible with different kinds of DEP substrates, which could expand the future application field of DEP microfluidic chips, including new forms of point-of care diagnostics and trapping circulating tumor cells.